ON WIRMAN’S ALLEGATION OF FALLACIES OF HARUN NASUTION THEOLOGICAL LOGIC (JOURNAL OF INDONESIAN ISLAM, 2023)
Theology has been employing logic in order to justify faith with reasons not to mention bridging a gap between some different theological schools of thoughts. This article aims to examine Wirman’s claim of fallacies against Nasution’s theological thought. Thus, I will investigate two questions: (1) What sort of fallacies does Wirman charge against Nasution? (2) If there is no specification, then would it be fallacies at any rate? To address these questions, I strive to capture Wirman’s main premise for identifying those fallacies, exploring Avicenna’s ḍarūrī, and discussing thirteen Aristotelian fallacies. On the one hand, the conclusion of this investigation might topple Wirman’s accusation, and on the other hand it might look like a consolation for Nasution. Having said that, both Wirman and Nasution do reason only in the realm of Aristotelian logic instead of Avicenna’s account of necessity.